Implementation Analysis of ISO 9001:2015 in the Food Industry: A Narrative Literature Review - Ima Nazmia; Esra Silalahi; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2023)
The purpose of this article is to conduct a narrative literature review of three articles discussing the implementation of ISO 9001:2015 in Food Industry Companies. The aim is to identify and summarize previously published articles without providing critical evaluation of the reviewed articles. The review findings indicate that Food Industry Companies have achieved quality improvement, performance enhancement, and continuous risk implementation to maintain service quality. The certification of the ISO 9001:2015 Quality Management System is used as a standard assessment indicator in achieving these objectives. The audit process consists of two stages: internal audit and visits by external certification bodies. The internal audit is coordinated by the Management Representative and conducted by 10 internal auditors who have been trained and qualified. The audit results are reported to management through management review meetings, and all agreed-upon corrective actions are implemented by the audited parties. ISO 9001:2015 is crucial in achieving quality standards, including for Small and Medium-sized Enterprises (SMEs), as it ensures quality, service, and customer satisfaction.